2010
DOI: 10.3109/00016340903505748
|View full text |Cite
|
Sign up to set email alerts
|

Environmental tobacco smoke exposure and perinatal outcomes: a systematic review and meta‐analyses

Abstract: Background. While active maternal tobacco smoking has well established adverse perinatal outcomes, the effects of passive maternal smoking, also called environmental tobacco exposure (ETS), are less well studied and less consistent. Objective: To determine to the effect of ETS on perinatal outcomes. Search strategy. Medline, EMBASE and reference lists were searched. Selection criteria. Studies comparing ETS-exposed pregnant women with those unexposed which adequately addressed active maternal smoking. Data col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
198
5
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 237 publications
(223 citation statements)
references
References 89 publications
14
198
5
2
Order By: Relevance
“…3 The main morbidity of infants were jaundice, chest infection, diarrhea and ear inflammation with statistically significant differences between exposed and non-exposed groups to ETS (X 2 = 15.16, p = 0. 01) ETS-exposed women have increased risks of infants with lower birth weight, congenital anomalies, longer lengths, and trends towards smaller head circumferences [15]. Cotinine level in children's urine statistically differentiated children from exposed homes compared with nonexposed homes [16].…”
Section: Discussionmentioning
confidence: 99%
“…3 The main morbidity of infants were jaundice, chest infection, diarrhea and ear inflammation with statistically significant differences between exposed and non-exposed groups to ETS (X 2 = 15.16, p = 0. 01) ETS-exposed women have increased risks of infants with lower birth weight, congenital anomalies, longer lengths, and trends towards smaller head circumferences [15]. Cotinine level in children's urine statistically differentiated children from exposed homes compared with nonexposed homes [16].…”
Section: Discussionmentioning
confidence: 99%
“…12,14,17,22,37 One study 10 confirmed that exposure to SHS during pregnancy was a cause of LBW and not merely an association. This study is consistent with previous studies indicating that exposure to SHS during pregnancy significantly reduced birthweight.…”
Section: Exposure To Secondhand Smoke During Pregnancy and Lbwmentioning
confidence: 99%
“…[51] Maternal exposure to second-hand smoke in pregnancy can also increase the risk of low-birthweight children. [52] Although quitting early in pregnancy will produce the greatest benefits, stopping at any stage during pregnancy yields benefits to the fetus and mother, and the child in the postnatal period. [53] Passive smoking increases the risk for asthma, middle ear and recurrent chest infections in children.…”
Section: Pregnancymentioning
confidence: 99%